Analysis of News Articles on the Central Java Tribune Online Media and Their Suitability as a Learning Source for Writing News Texts - Prayogo, Ilham Rif’an; Utami, Santi Pratiwi Tri (J-LELC: Journal of Language Education, Linguistics, and Culture, 2024)
This research focuses on examining the content, structure, linguistic rules of news texts contained in online mass media and their suitability to be used as a learning resource for writing news texts. The research objectives are 1) Describe the content, structure and linguistic rules of the news text in the September 2023 edition of Tribun Jateng. 2) Describe the suitability of the news text in the September 2023 edition of Tribun Jateng as an alternative learning resource. This research uses a theoretical and methodological approach in the form of news text theory and learning sources as well as a methodological approach in the form of qualitative descriptive methods. The results of this research show that there are as many as 6 elements of news text, namely what, where, when, who, why and how, 3 news text structures, namely head of news, body of news and tail of news, 6 linguistic rules of news text, namely the use of standard language. , use of direct sentences, use of the conjunction that, use of mental verbs, use of adverbial functions of time, and use of temporal conjunctions. The results of the second research from 9 news text data contained in the September 2023 edition of the Tribun Jateng online media showed that there were 8 news texts suitable for use as learning resources.